ERRORS IN QQ ONLINE CHATTING: A STUDY ON CHINESE ESL LEARNERS IN INDONESIAN UNIVERSITY - Rohayati, Desi; Abidasari, Erlyna (University of Muhammadiyah Malang, 2019)
This study intends to investigate errors found in an online written platform used by Chinese students in English Language Education Department. The online platform observed in this study was QQ chatting, where students freely and without pressure utilize the application for everyday English communication. Most Chinese students have performed unorganized sentence patterns, resulting in meaning breakdown. This study employed qualitative case study design with five Chinese respondents. The researchers were actively involved in the QQ chatting as the participants; the discussion topics revolved around everyday communication topics, namely academic life, friendship, social interaction, and culture challenges. The data then were recorded weekly for one semester and analyzed through manuscript analysis from the recorded captures of the conversations. The findings suggest that there were various types of errors performed by Chinese students: omission, misformation, addition, misordering, and mixed-types. The most prominent one was omission with the total of twenty-eight times occurrence. The omission errors were divided into omission of nouns as in ‘today have sunshine’, omission of verbs as in ‘I don’t know here will so cold’, omission of auxiliary verbs as in ‘I eaten dinner’ and omission of verb inflections as in ‘Where are you go?’.The most commonly found omissions errors were due to the influence of Chinese first language where the speakers have totally different tenses and sentence organization with English.